Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 50 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Falco peregrinus peregrinator Sundevall, 1837" ] } The dataset includes 50 records from 16 constituent datasets: 2 records from iNaturalist Research-grade Observations. 8 records from Field Museum of Natural History (Zoology) Bird Collection. 2 records from University of Michigan Museum of Zoology, Division of Birds. 10 records from WFVZ Bird Collections. 5 records from AMNH Bird Collection. 4 records from ORN. 1 records from Lund Museum of Zoology (MZLU). 1 records from LACM Vertebrate Collection. 1 records from IndOBIS, Indian Ocean Node of OBIS. 5 records from Naturalis Biodiversity Center (NL) - Aves. 1 records from Xeno-canto - Bird sounds from around the world. 1 records from RBINS DaRWIN. 1 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Natural History Museum (London) Collection Specimens. 6 records from Museum of Comparative Zoology, Harvard University. 1 records from Collection Ornithologie - SNSD. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences